2021
DOI: 10.1101/2021.12.08.471708
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Distribution map of peristaltic waves in the chicken embryonic gut reveals importance of ENS and inter-region cross talks along the gut axis

Abstract: Gut peristaltic movements recognized as the wave-like propagation of a local contraction are crucial for effective transportation and digestion/absorption of ingested materials. Although the physiology of gut peristalsis has been well studied in adults, it remains largely unexplored how the cellular functions underlying these coordinated tissue movements are established along the rostral-caudal gut axis during development. The chicken embryonic gut serves as an excellent experimental model for elucidating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…To understand the gut peristaltic movements, which reiterate at specific sites along the gut axis (Shikaya et al, 2022), deciphering the mechanisms underlying the coordination/synchronization of oscillators among multiple cells is critical. Exploiting the finding obtained in the current study that multiple organoids easily fuse each other in vitro, we have found that two organoids with different oscillatory rhythm eventually coordinate their phases upon the fusion (Fig.…”
Section: The Gut Contractile Organoid Provides a Useful Model And Too...mentioning
confidence: 99%
See 2 more Smart Citations
“…To understand the gut peristaltic movements, which reiterate at specific sites along the gut axis (Shikaya et al, 2022), deciphering the mechanisms underlying the coordination/synchronization of oscillators among multiple cells is critical. Exploiting the finding obtained in the current study that multiple organoids easily fuse each other in vitro, we have found that two organoids with different oscillatory rhythm eventually coordinate their phases upon the fusion (Fig.…”
Section: The Gut Contractile Organoid Provides a Useful Model And Too...mentioning
confidence: 99%
“…Thus, it is tempting to speculate that during early gut peristalsis, ICCs might receive feedback from their governing SMCs to generate more stable coordination of pace-making activity among ICCs. Indeed, we have previously reported that in the very early embryonic gut, origins of peristaltic wave (OPW) are randomly distributed along the gut axis, but they later become confined to specific sites showing that ICCs undergo more stable and coordinated pace-making (Shikaya et al, 2022).…”
Section: Possible Feedback From Smc's Contractility To Icc's Oscillat...mentioning
confidence: 99%
See 1 more Smart Citation